AN INFLUENCE OF SUPERVISION, WORKLOAD AND WORK STRESS TO PERFORMANCE INPATIENT INSTALLATION NURSES AT MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Widya Panduwinata; Ermi Girsang; Sri Wahyuni Nasution (Jurnal Scientia, 2023)
The large number of public demands for nursing services and the emergence of competition in many health service facilities urge hospital management to always improve nursing services by increasing nurse performance. This is because nurses are the health workers with the largest number and are on duty 24 hours a day to serve patients, especially nurses who are tasked with providing nursing services in inpatient installations. There are many previous studies that examine factors that influence nurses' performance in nursing services. In this research, we want to know the influence of supervision, workload and work stress on the performance of inpatient installation nurses at Murni Teguh Memorial Hospital Medan. This research is a quantitative research with a cross sectional approach. The population is all 224 health workers (nurses) who work in inpatient installations and all of them were used as samples. Data collection techniques include distributing questionnaires, documentation and literature study. The analysis method uses univariate, bivariate and multivariate analysis using multiple linear regression equations. The results of the research show that supervision, workload and work stress influence nurse performance and the supervision variable is the dominant influence. The research conclusion is that supervision, workload and work stress influence the performance of inpatient installation nurses at Murni Teguh Memorial Hospital Medan. It is recommended that the head of the room should provide routine supervision in an effort to guide and direct nurses so that they have good competence in carrying out nursing service tasks more effectively and efficiently.